258 The challenges of creating a fellowship in gynecologic oncology in mozambique, a country with no formal training program in gynecologic oncology. (18th September 2019) - Rangeiro, R; Changule, D; Daude, S; Ribeiro, M; Luis, E; Mabota, F; Cintra, G; Moretti-Marques, R; Lopes, A; Vieira, M; Salcedo, M; Baker, H; et al.
Abstract : Objectives: Mozambique has a high prevalence of gynecologic cancers and has no trained gynecologic oncologist or specialized training program. There are challenges associated with creating a training program. Methods: The International Gynecologic Cancer Society (IGCS) Gynecologic Oncology Global Curriculum & Mentorship Program, a two-year program to train gynecologists in gynecologic oncology in countries without training programs, includes self-study, assessments and surgical training with international mentors. The program uses the Project ECHO (Extension for Community HealthCare Outcomes) telementoring model for monthly tumor boards. Fellows present cases, discuss management with international mentors from Brazil and the US, and receive didactic lectures. Fellows record cases in REDCap, a web database, and travel to Brazil for additional study. Results: Prior to this program there were limited options for surgical treatment of women with gynecologic tumors in Mozambique. Developing support and resources for a new training program requires fellows and mentors to clearly explain the program to hospital and Ministry of Health leadership. The fellows in Mozambique developed strategies to work and learn together, particularly in the operating room. A senior gynecology faculty member is the local mentor. The program, initiated in 2017, has matured as administrative and resource challenges have been successfully met. Conclusions: This program offers a unique opportunity to build a specialty training program with support from an international society and experienced clinicians and lays the foundation to develop a training program. Knowledge, surgical skills and patient care has improved. Patients with gynecologic cancers can now receive care locally, including surgery.